Collaboration Around Rare Bone Diseases Leads to the Unique Organizational Incentive of the Amsterdam Bone Center - Eekhoff, Elisabeth M. W.; Micha, Dimitra; Forouzanfar, Tymour; de Vries, Teun J.; Netelenbos, J. Coen; Klein-Nulend, Jenneke; van Loon, Jack J. W. A.; Lubbers, Wouter D.; Schwarte, Lothar; Schober, Patrick; Raijmakers, Pieter G. H. M.; Teunissen, Bernd P.; et al. (Frontiers in Endocrinology, 2020)
In the field of rare bone diseases in particular, a broad care team of specialists embedded in multidisciplinary clinical and research environment is essential to generate new therapeutic solutions and approaches to care. Collaboration among clinical and research departments within a University Medical Center is often difficult to establish, and may be hindered by competition and non-equivalent cooperation inherent in a hierarchical structure. Here we describe the “collaborative organizational model” of the Amsterdam Bone Center (ABC), which emerged from and benefited the rare bone disease team. This team is often confronted with pathologically complex and under-investigated diseases. We describe the benefits of this model that still guarantees the autonomy of each team member, but combines and focuses our collective expertise on a clear shared goal, enabling us to capture synergistic and innovative opportunities for the patient, while avoiding self-interest and possible harmful competition.